(untitled) (Research, Society and Development, 2020)
The search for foods with a different flavor and less use of additives makes the sourdough bread a promising technology. In addition, adding fruit to bread is a way of obtaining products with interesting technological, sensory, nutritional and functional aspects. Thus, the objective of this research was to make bread using natural fermentation (sourdough) and jaboticaba. Four sourdough were prepared, whole and refined, with and without the addition of jaboticaba. The doughs were fed for 16 days and used as an inoculum for the bread fermentation. Two standard formulations were also prepared, one integral and one refined, totaling six formulations. The sourdough was evaluated for pH and lactic bacteria and breads for specific volume, humidity, total acidity, pH, instrumental texture, water activity, image evaluation of slices, antioxidant capacity and sensory evaluation. The data obtained were submitted to ANOVA and the means to the Tukey t test. Breads with sourdough had lower specific volumes and greater acidity compared to standard formulations. The use of whole meal flour, sourdough and jaboticaba resulted in greater antioxidant capacities. The coloring of the breads with jaboticaba distanced itself a lot from the standard formulation, which caused a strangeness on the part of consumers, who evaluated these breads with lower grades for coloration, appearance, overall impression and purchase intention, although, from the grades obtained, can still be considered as well accepted.